Population administration service satisfaction in Lima Puluh Kota District, West Sumatera - Meironi Meironi; Werry Darta Taifur; Nasri Bachtiar (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
Assessment of public satisfaction with an agency's performance that organizes public services needs to be assessed by involving all service attributes because service attributes cannot stand alone, and performance improvement cannot be made separately. Assessment of service attributes is one way to track consumer ratings so that service providers can understand the causes of service problems. This study uses the Importance Performance Analysis (IPA) method. From this study, it was found that the priority that needs to be improved to improve public satisfaction with population administration services is to increase the discipline of officers in serving the community, certainty of service costs, and speed of service.